Pengaruh Kompetensi Pedagogik Dosen terhadap Motivasi Belajar Mahasiswa Pendidikan IPS - Akhmad Munaya Rahman; Mutiani Mutiani; M. Adhitya Hidayat Putra (IAI Darussalam, 2019)
The purpose of this study was to determine the effect of lecturer pedagogic competence on learning motivation of Social Studies Department FKIP ULM students. The research method is used a quantitative approach. The research subjects consisted of 150 social studies students with full sampling. The data collection methods in the form of observation, literature study, documentation, and questionnaires. The data analysis was done by percentage techniques and simple linear regression analysis with the help of SPSS 16 for windows. The results showed that the pedagogic competence of lecturers was in the good category at 82.4%, the learning motivation of students was in the sufficient category of 74.5%. The results of simple linear regression analysis show that tcount (5.712)> t table (1.976), it can be stated that the hypothesis test Ho is rejected and Ha is accepted. This study can be concluded that the pedagogical competence of lecturers has a significant influence on student learning motivation.